GE_GERICHTE P/4241/2020 vom 23. März 2022 - GE Cour de justice (2022)
CLASSEMENT DE LA PROCÉDURE;GESTION DÉLOYALE;RÉTROCESSION(PRODUITS FINANCIERS);MANDATAIRE;OBLIGATION DE RENSEIGNER | CPP.319; CP.158; CO.398.al2; CO.400